Propuesta de Modelo de Gestión de Mantenimiento para el Área Lavandería Central de la Caja Costarricense del Seguro Social - Villegas-Méndez, Luis Alfredo (Instituto Tecnológico de Costa Rica, 2016)
This project presents a proposal for a Maintenance Management Model for the Central Laundry Area of the CCSS. This management seeks to improve the current situation of the Sub-area of the laundry area maintenance workshop. First, an evaluation to determine the maturity of the Maintenance Subarea, based on the Venezuelan Standard COVENIN 2500-93, which uses a quantitative method to measure the maintenance management of those currently operating companies. This method contemplates the evaluation of four large sectors in the industry, which are:  Organizations of the company  Organization of the duties of maintenance.  Planning, programming and control of maintenance activities  Competence of staff Currently, the Maintenance Department does not have the tools to rate its management, for which an internal maintenance audit will be carried out. The purpose of this audit is to provide the department with a broader picture of the gaps that exist between an ideologized department and the one being evaluated. For the development of the maintenance management model, a diagram or roadmap is proposed for the follow-up of the processes for continuous improvement, this diagram is responsible for linking the processes that have been considered necessary to obtain the best results of the management from the inputs or resources it receives. After defining which processes are acting in the Sub-Area of Maintenance and their relationship to each other with the management, a series of procedures are presented viii by the Institutional Maintenance Area in conjunction with the Area of Building Administration so that the implementation of the model is given in a standardized format for the maintenance área of the CCSS. In view of the problems that could endanger the continuity of the laundry service due to an inadequate management of the maintenance activities, a study is proposed to evaluate the need for human resources or the capacity of the personnel available in the department, in order to verify in a quantitative way if there is enough staff to perform preventive and corrective maintenance to each team. In this way the maintenance manager can justify the maintenance planning and assign the tasks according to the available human resource capacity. In addition, if necessary, the assignment of new staff to the Maintenance Subarea may be assessed jointly with the administration.

En este proyecto se presenta una propuesta de un Modelo de Gestión de Mantenimiento para el Área de Lavandería Central de la CCSS. Esta gestión busca mejorar la situación actual del Subárea del taller de mantenimiento del Área de Lavandería, se inicia con una evaluación para determinar la madurez del Subárea de Mantenimiento, basándose en la Norma Venezolana COVENIN 2500-93, la cual utiliza un método cuantitativo para medir la gestión de mantenimiento en aquellas empresas en operación. Este método contempla la evaluación de cuatro grandes sectores de la industria, los cuales son:  Organización de la empresa  Organización de la función de mantenimiento  Planificación, programación y control de las actividades de mantenimiento  Competencia del personal Actualmente el Departamento de Mantenimiento no cuenta con herramientas para calificar su gestión, por la cual se procederá a realizar una auditoría interna de mantenimiento. El fin de dicha auditoría es brindarle al departamento una visión más amplia de las brechas que existen entre un departamento idea y el que se está evaluando. Para el desarrollo del modelo de gestión de mantenimiento, se plantea un diagrama o hoja de ruta para el seguimiento de los procesos en pro de la mejora continua, dicho diagrama se encarga de enlazar los procesos que se han considerados necesarios para lograr obtener los mejores resultados de la gestión a partir de los insumos o recursos que esta reciba. Luego de definir cuáles procesos son los que actúan en el Subárea de Mantenimiento y su relación entre sí con la gestión, se presenta una serie de procedimientos planteados por el Área de Mantenimiento Institucional en conjunto con el Área de Administración de Edificios para que la implementación del modelo se dé en forma estándar en las unidades de mantenimiento de la CCSS. Ante la problemática que podría generar poner en riesgo la continuidad del servicio de lavandería a raíz de una inadecuada gestión de las actividad de mantenimiento, se plantea realizar un estudio sobre la necesidad de recursos humano o capacidad del personal disponible en el departamento, esto con el fin de verificar de manera cuantitativa si realmente se cuenta con el personal suficiente para realizar el mantenimiento preventivo y correctivo a cada equipo. De esta manera el encargado de mantenimiento podrá justificar la planificación del mantenimiento y asignar las tareas de acuerdo con la capacidad de recurso humano disponible. Además, de ser necesario, se podrá valorar conjuntamente con la administración la asignación del nuevo personal al Subárea de Mantenimiento.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2016.
Keywords: Evaluación; Procesos; Procedimientos; Organización Empresarial; Planificación; Auditoría; Research Subject Categories::TECHNOLOGY::Industrial engineering and economy::Industrial organisation, administration and economics